Wages and Profits in the Paper Industry, 1929-1939 - Maclaurin, W. Rupert (Quarterly Journal of Economics, 1944)
I. The problem, 196.— II. Description of the industry, 198.— III. Description of the sample, 199. — IV. Timing of wage changes, 199.— Comparisons: regions and types of products, 205; ability to pay, 206; size of company, 210; unionization, 211; dividend changes, 212; summary, 213. — V. Wage-rate levels: the data, 214; ranking and grouping of mills, 214. — Comparisons: products and states, 215; profitability and financial condition, 219; size of company, 221; unionization, 222; community, 223. — Conclusions, 224.